WEB-BASED DIGITAL DOCUMENT GOVERNANCE SYSTEM FOR OPTIMIZING MULTI-AGENCY COMPLIANCE MONITORING: AN EMPIRICAL STUDY AT TEGAL CITY PPID - Rahmat Afandi; Nurmalasari Nurmalasari (LPPM Universitas Nusa Mandiri, 2026)
Information and documentation management at the Public Information and Documentation Management Office of Tegal City faces operational challenges due to reliance on manual mechanisms for collecting files from 73 Regional Government Agencies. The main obstacles include slow recapitulation processes that can take up to four weeks, high risk of damage or loss of physical archives, and difficulty in monitoring document submission status in real time. This study aims to design and implement a web-based information system that optimizes the workflow of collecting, verifying, and monitoring public document compliance across government agencies within the digital governance infrastructure of Tegal City PPID. The system was developed using the Waterfall model which includes requirement analysis, system and data design, coding, testing, and maintenance. System modeling was carried out using Unified Modeling Language to visualize system functions and data structures. The resulting system integrates workflows between 73 Regional Government Agencies and the PPID through a centralized platform that allows operators to upload documents independently and administrators to conduct verification processes. The system also provides a monitoring dashboard to track document submission compliance in real time. System validation was conducted using Black-box Testing on 11 functional scenarios with a success rate of 100%, and User Acceptance Testing confirming system acceptance based on seven evaluation criteria. The implementation of this system improves efficiency in document management, reduces the risk of data loss, and supports more effective public information services.